2020
DOI: 10.1093/heapol/czaa078
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to strengthen the leadership capabilities of health professionals in Sub-Saharan Africa: a scoping review

Abstract: Leadership is a critical component of a health system and may be particularly important in Sub-Saharan Africa, where clinicians take on significant management responsibilities. However, there has been little investment in strengthening leadership in this context, and evidence is limited on what leadership capabilities are most important or how effective different leadership development models are. This scoping review design used Arksey and O’Malley’s approach of identifying the question and relevant studies, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…Health system supervisors are often clinicians with little or no formal leadership or management training. 29 Several studies have found associations between leadership and management skills of health system supervisors and health outcomes, including childhood vaccination and primary care delivery. 30 , 31 The leadership and management training we provided might have contributed to intervention effectiveness by improving competence in these areas and offering concrete tools to apply these skills.…”
Section: Discussionmentioning
confidence: 99%
“…Health system supervisors are often clinicians with little or no formal leadership or management training. 29 Several studies have found associations between leadership and management skills of health system supervisors and health outcomes, including childhood vaccination and primary care delivery. 30 , 31 The leadership and management training we provided might have contributed to intervention effectiveness by improving competence in these areas and offering concrete tools to apply these skills.…”
Section: Discussionmentioning
confidence: 99%
“…While leadership and governance are central to the success of any endeavor to improve the quality of care, their role and impact in advancing hypertension care in SSA are not widely researched, and the few existing studies are predominantly of poor quality [96]. Thornton highlighted the critical values of leadership commitment, willingness to fund care, strategic and creative local and foreign partnerships, and evidence-based guidelines as the key reasons why Botswana surpassed the United Nations’ HIV management goals of 95% awareness, 95% on treatment, and 95% [81].…”
Section: Discussionmentioning
confidence: 99%
“…While much of the emphasis was on building leadership capacity, the project included management capacity as there was an observed need for improvement in this area as well. In a scoping review of leadership programs in Sub-Saharan Africa, Johnson and colleagues [ 36 ] found that many of the programs combined leadership and management capacity building, which they concluded was reasonable, given than the leaders within the health facilities are also, in many instances, managers who must oversee both change and performance.…”
Section: Discussionmentioning
confidence: 99%